Boosting High‐Voltage and Ultralong‐Cycling Performance of Single‐Crystal LiNi0.5Co0.2Mn0.3O2 Cathode Materials via Three‐in‐One Modification. Issue 1 (9th March 2022) - Zhang, Bao; Shen, Jixue; Wang, Qi; Hu, Changqing; Luo, Bi; Liu, Yun; Xiao, Zhiming; Ou, Xing
Abstract : LiNi0.5 Co0.2 Mn0.3 O2 is extensively researched as one of the most widely used commercially materials for Li‐ion batteries at present. However, the poor high‐voltage performance (≥4.3 V) with low reversible capacity limits its replacement for LiCoO2 in high‐end digital field. Herein, three‐in‐one modification, Na‐doping and Al2 O3 @Li3 BO3 dual‐coating simultaneously, is explored for single‐crystalline LiNi0.5 Co0.2 Mn0.3 O2 (N‐NCM@AB), which exhibits excellent high‐voltage performance. N‐NCM@AB displays a discharge‐specific capacity of 201.8 mAh g −1 at 0.2 C with a high upper voltage of 4.6 V and maintains 158.9 mAh g −1 discharge capacity at 1 C over 200 cycles with the corresponding capacity retention of 87.8%. Remarkably, the N‐NCM@AB ||graphite pouch‐type full cell retains 81.2% of its initial capacity with high working voltage of 4.4 V over 1600 cycles. More importantly, the fundamental understandings of three‐in‐one modification on surface morphology, crystal structure, and phase transformation of N‐NCM@AB are clearly revealed. The Na + doped into the Li–O slab can enhance the bond energy, stabilize the crystal structure, and facilitate Li + transport. Additionally, the interior surface layer of Li + ‐ions conductor Li3 BO3 relieves the charge transfer resistance with surface coating, whereas the outer surface Al2 O3 coating layer is beneficial for reducing the active materials loss and alleviating the electrode/electrolyte parasite reaction. This three‐in‐one strategy provides a reference for the further research on the performance attenuation mechanism of NCM, paving a new avenue to boost the high‐voltage performance of NCM cathode in Li‐ion batteries. Abstract : Three‐in‐one modification, Na‐doping and Al2 O3 @Li3 BO3 dual‐coating simultaneously, is explored for single‐crystalline LiNi0.5 Co0.2 Mn0.3 O2 (N‐NCM@AB), which exhibits excellent cathode properties, paving a new avenue to boost the high‐voltage performance of NCM cathode in lithium‐ion batteries.